Validity Test For Simple Ergonomics Risk Assessment (SERA) Method - Ezrin Hani, Sukadarin; Baba, M. Deros; Jaharah, A. Ghani; Ahmad Rasdan, Ismail; Nursyazwani, Mohd Nawi; Norhidayah, Abdull (Malaysian Public Health Physicians’ Association, 2016)
Validity test is important during the development of ergonomics measurement. Failure to conduct validity tests will result in the measurement method being developed to be incapable of providing reliable ergonomics measurements. The objective of this study is to conduct validity test on the simple method ergonomics measurement which was developed. The method named Simple Ergonomics Risks Assessment (SERA). Content validity test and criterion validity test were conducted. The content validity test consists of 6 ergonomics experts who actively provide inputs and positive feedbacks to improve the measurement method being developed. Meanwhile, the criterion validity test involves data collection of complaints on body parts among oil palm workers which were derived from Nordic Musculoskeletal Questionnaire (NMQ) and ergonomics risk assessment scores obtained from SERA. Both findings were tested with the Chi-square test to explore possible relations between the two findings. Results from the test conducted showed that there are significant relations in the scores of neck posture; hip, right and left shoulder, right and left wrists and the right hand associated with fresh fruit bunch (FFB) harvesting activities. In the loose fruits collection, the Chi-square test showed significant relations in the scores of neck posture, hip, right and left shoulders, right wrist, right arm and the left hand. However, there are body parts such as the legs which showed no significant relation. More tests should be conducted to further explore the validity of the method being developed. Findings from both validity tests show that SERA were verified by the experts and tested with validated method so that it is valid to be applied in the future.